2018
DOI: 10.1167/tvst.7.6.23
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Toxicity of Intravitreal Injection of Ziv-Aflibercept in Albino Rabbits

Abstract: PurposeTo evaluate retinal toxicity of ziv-aflibercept, a drug that had been approved for use for patients with colon cancer.MethodsTwenty-two albino rabbits were injected intravitreally with 0.1 mL of ziv-aflibercept solution into the experimental eye and 0.1-mL saline into the control eye. Twelve were used for electroretinogram (ERG) at 4-weeks follow-up. An additional 10 rabbits were used for testing penetration of ziv-aflibercept into the retina during follow-up. The visual-evoked potential (VEP) was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The limitations of this study were the model used, the scarce number of subjects in each group per product and number of intravitreal injections administered. The albino condition of the species used does modify the retinal response in the ERG due to scatter and reflection at the retinal layer [19,20]. However, the fact that this was a comparative evaluation between PRO-169 and ranibizumab in the same animal model parallels the results and attests to the value of the correlation of the studied parameters.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The limitations of this study were the model used, the scarce number of subjects in each group per product and number of intravitreal injections administered. The albino condition of the species used does modify the retinal response in the ERG due to scatter and reflection at the retinal layer [19,20]. However, the fact that this was a comparative evaluation between PRO-169 and ranibizumab in the same animal model parallels the results and attests to the value of the correlation of the studied parameters.…”
Section: Discussionmentioning
confidence: 55%
“…The amplitude ratio (experimental/control) served as an index of PRO-169 and ranibizumab effect on photopic retinal function. To assess retinal response, the data obtained at each ERG recording session was derived to the entire response-stimulus energy relationship and the V Max ratio (experimental/control eye) and the semi saturation constant difference (experimental–control) of the dark-adapted b-waves were calculated [ 19 ]. Previous studies have reported that with this approach, technical factors such as depth of anesthesia and duration of adaptation did not affect the evaluation of retinal function [ 12 , 13 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the end of exposure and wash-out time, however, no reduction compared to baseline measurements could be detected. Short-term animal studies have not found retinal toxicity with ERG in the retina of rabbits with aflibercept at 4-week or ziv-aflibercept at 2-week follow-up [36,37]. Six-month and 1-year follow-up of 15 eyes of nAMD patients treated with ziv-aflibercept have not shown signs of toxicity on ffERG [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐two albino rabbits (weighing 1.5–3 kg) each received a single 0.1 ml ziv‐aflibercept injection and a control group received normal saline (Ramon et al. ). Dark‐adapted electroretinograms showed no signs of damage in both groups at one and 4 weeks, and visual evoked responses were of normal pattern and amplitude at 4 weeks.…”
Section: Animal and Preclinical Studiesmentioning
confidence: 99%